A P-doped PtTe mesoporous nanotube electrocatalyst. Issue 6 (9th April 2020) - Wang, Ziqiang; Zhang, Hugang; Yin, Shuli; Liu, Songliang; Dai, Zechuan; Xu, You; Li, Xiaonian; Wang, Liang; Wang, Hongjing
Abstract : We report a dual-template method for synthesizing mesoporous P-doped PtTe nanotubes using trioctylphosphine as the phosphorus dopant towards methanol oxidation. Abstract : The design of active and stable electrocatalysts for the methanol oxidation reaction (MOR) plays a vital role in the large-scale commercialization of direct methanol fuel cells. Herein, one-dimensional P-doped PtTe nanotubes with uniform mesoporous shells (P-PtTe MNTs) have been synthesized using F127 and Te nanowires as the dual template and trioctylphosphine as the phosphorus dopant. The resultant P-PtTe MNTs with sufficient exposed surface atoms can improve the atom utilization of Pt. Moreover, the incorporation of P atoms into Pt lattices can tailor the electronic structure of Pt and induce a strong synergic effect, thus leading to highly active and durable performance for the MOR. This phosphorus doping is very valuable for controllable synthesis of various metal–nonmetal catalysts with desired morphologies.